Pengembangan Model Elaborasi Untuk Kecakapan Text Writing Melalui Audio Visual Pada Pelajaran Bahasa Inggris - Aprizal, -; Umar, Syahwani; Usman, Andi (Jurnal Pembelajaran Prospektif, 2016)
Aims to help teachers of English in overcoming difficulties and student learning in English lessons . Efforts English teacher with the development model through the elaboration of Media Audio Visual . Techniques of collecting data using questionnaires , observation and interviews . Implementation of the trial , as well as the acquisition of skills competency test text writing . All data collected were analyzed quantitatively and qualitatively using a simple matter of percentages . Based on the results of the discussion can be concluded that the results " Development of a model elaboration for proficiency text writing with media Audiovisual in the subjects of English Class X Administration Department SMK Negeri 2 Singkawang " which includes the design development models elaboration , procedures for use use models elaboration , as well as the impact of Media Valid audio- visual that is based on the display content, the learning aspect and the aspect programan.